2004
DOI: 10.1002/bip.20103
|View full text |Cite
|
Sign up to set email alerts
|

A study of the conformations of valinomycin in solution phase

Abstract: Vibrational absorption and vibrational circular dichroism (VCD) spectra of valinomycin are measured, in different solvents, in the ester and amide carbonyl stretching regions. The influence of cations, namely Li(+), Na(+), K(+), and Cs(+), in methanol-d(4) solvent is also investigated. Ab initio quantum mechanical calculations using density functional theory and 6-31G* basis set are used to predict the absorption and VCD spectra. A bracelet-type structure for valinomycin that reproduces the experimental absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 49 publications
3
57
0
Order By: Relevance
“…[5][6][7][8][9][10][11][12][13][14][15][16] It should thus require a certain ion radius, ideally that of K þ (or larger). This idea has been supported by the known difference of three to four orders of magnitude between the stability constants of the K þ and Na þ complexes of valinomycin [17][18][19] and thus led to the conclusion that the structure of the latter complex must be different.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[5][6][7][8][9][10][11][12][13][14][15][16] It should thus require a certain ion radius, ideally that of K þ (or larger). This idea has been supported by the known difference of three to four orders of magnitude between the stability constants of the K þ and Na þ complexes of valinomycin [17][18][19] and thus led to the conclusion that the structure of the latter complex must be different.…”
Section: Discussionmentioning
confidence: 99%
“…This idea has been supported by the known difference of three to four orders of magnitude between the stability constants of the K þ and Na þ complexes of valinomycin [17][18][19] and thus led to the conclusion that the structure of the latter complex must be different. 16 An even more different structure should thus be expected in the case of the proton complex (although, owing to the presence of small amounts of water, the proton is probably present in the form of hydroxonium ion H 3 O þ ). However, the shifts of the 1 H NMR signals and changes of the 3 J NHCH splitting constants observed by us under H þ coordination are quite analogous to those observed [5][6][7][8][9][10] with K þ , thus indicating that the conformation of valinomycin and thus the structure of the complex are virtually the same in both cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our Raman studies confirmed the existence of β-type hydrogen bonding when gramicidin A was solubilized in a hydrophobic solvent similar to the hydrophobic interior of lipid bilayers. Many subsequent vibrational studies have been made on both VM and Gramicin A [60,169,244,248].…”
Section: Initial Studies Of Model Ion Carriers and Channelsmentioning
confidence: 99%